(untitled) (مجلة المنصور, 2023)
The scope of this work is to focus on the work injuries caused by long time computer uses and to elaborate the tasks of ergonomics related to personnel’s activities. Consequently, to minimize the defects emanate due to the long period computer usage. Furthermore, this research is aiming to identify and analyze the relationship between ergonomics and shoulders, neck, backbone and eyes pains for the computer centers personnel Many conclusions have been drawn based on the outcomes of this research. Mainly, inconsistency in the technical specification between the computer centers and the standards of ergonomics, besides the weakness of the administration system in realizing the personnel’s suffer due to this type of effectives. Finally, the author recommends to afford the suitable environment by the responsible positions based on the ergonomics standard and to encourage the personnel to acclimatize with those bases.